Stabilization of linear descriptor systems by state-feedback controllers - Kaczorek, Tadeusz (1932- ) (Zielona Góra: Uniwersytet Zielonogórski)
The necessary and sufficient conditions are established for the existence of a solution to the stabilization problem for linear continuous-time descriptor systems. A new procedure is presented for designing a state-feedback controller such that the closed-loop system is asymptotically stable and its response is impulse-free.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka